2015
DOI: 10.3892/ol.2015.3689
|View full text |Cite
|
Sign up to set email alerts
|

miR-128 downregulation promotes growth and metastasis of bladder cancer cells and involves VEGF-C upregulation

Abstract: Abstract. serves an important role in regulating growth, invasiveness, stem cell-like traits, differentiation and apoptosis of different types of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Padera et al (23) demonstrated that a high expression of VEGF-C facilitates lymphatic vessel hyperplasia surrounding tumors and lymphatic metastasis, but there are no functional lymphatic vessels within tumors, suggesting that functional lymphatic vessels that surround tumors are sufficient for lymphatic metastasis. In the present study, the expression of VEGF-C mRNA and protein in the bladder cancer tissues is significantly higher than normal tissues, being consistent with previous studies (24,25). Similar results were obtained from blood and urine samples from patients with bladder cancer, suggesting that changes in VEGF-C expression are associated with the occurrence and development of bladder cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Padera et al (23) demonstrated that a high expression of VEGF-C facilitates lymphatic vessel hyperplasia surrounding tumors and lymphatic metastasis, but there are no functional lymphatic vessels within tumors, suggesting that functional lymphatic vessels that surround tumors are sufficient for lymphatic metastasis. In the present study, the expression of VEGF-C mRNA and protein in the bladder cancer tissues is significantly higher than normal tissues, being consistent with previous studies (24,25). Similar results were obtained from blood and urine samples from patients with bladder cancer, suggesting that changes in VEGF-C expression are associated with the occurrence and development of bladder cancer.…”
Section: Discussionsupporting
confidence: 81%
“…miR‐128 was reported as oncogene or tumour suppressor in various cancers. For example, miR‐128 was reported to be downregulated in cancer tissues and represses growth and metastasis of bladder cancer, lung cancer, and glioblastoma multiforme . However, different studies of the miR‐128 in carcinoma reported discordant conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…First, we evaluated the cell toxicity exerted by EVOOE on two different BCa cell lines, T24 and 5637, which are characterized by two different grades and are widely used as in vitro models (3133) as they cover the more frequent subtypes of BCa. 5637 cells well represent the E2F3/RB1 pathway due to amplification of 6p22.3, concomitant with loss of one copy of RB1 and mutation of the other copy.…”
Section: Discussionmentioning
confidence: 99%